Changes in Electrophoretic patterns of Sarcoplasmic Proteins and Myofibrillar Proteins in Caranx melampygus (Cuvier, 1833) during chilled storage - Hassan, Femeena; Nija, K. V. (Fishery Technology, 2020)
SDS-PAGE studies were conducted to apprehend the changes in the electrophoretic pattern of myofibrillar and sarcoplasmic proteins of Caranx melampygus (Cuvier, 1833) (Blue fin Trevally) during chilled storage. The study revealed that the intensity of Myosin bands were getting reduced during storage. The relative front of myosin band was getting decreased during storage.The relative front on initial day for myosin is 0.331 and it decreased to 0.303 on 12thday of storage. In protein profile, molecular weights of protein bands were found to be 191.8kDa, 99.1 kDa, 52.0 kDa for myofibrillar proteins on initial day, and 200.0 kDa, 101.4 kDa, 51.5 kDa on 12th day. Molecular weights of protein bands were found to be 97.4 kDa, 60.3 kDa, 50.9 kDa, 30.4 kDa, 29.2 kDa, 26.8 kDa, 25.6 kDa, 21.5 kDa for sarcoplasmic proteins on initial day and 97.4 kDa, 61.1 kDa, 52.1 kDa, 45.8 kDa, 34.6 kDa, 30.0 kDa, 26.1 kDa ,21.5 kDa respectively on 12th day. The number of bands for sarcoplasmic proteins and myofibrillar proteins of Caranx melampygus were same on initial day and final day of storage (9 and 3 respectively).